PENGARUH TINGKAT SUKU BUNGA BI RATE, JUMLAH UANG BEREDAR DAN NERACA PEMBAYARAN TERHADAP NILAI TUKAR RUPIAH TAHUN 2006-2015 - Irvany Eris; Tri Sukirno Putro; Sri Endang Kornita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the effect of interest rate bi rate, money supply and balance of payments on the exchange rate in 2006-2015. This study uses secondary data types. secondary data obtained from agencies involved in the research. methods of analysis in this research is quantitative descriptive, using Multiple Linear Regression Analysis. The results showed that the partial interest rate bi rate positive and significant effect on the exchange rate obtained from Tcount 3.397 > Ttable 2.447 and 0.015 significance or probability below 0.05, the money supply is positive and significant impact on the rupiah yangdidapat of Tcount 7,680 > 2,447 Ttabel with significant value 0,000 or probability below 0.05, the balance of payments and no significant negative effect on the exchange rate obtained from Tcount -0908 < Ttabel 2.447 to 0.399 or the probability of a significant value above 0.05, and simultaneous bi-rate interest rates, money supply and the sheer number of balance of payments effect on the exchange rate obtained on the value of F 21.406 > F table 4.76, with significant value 0.001 < 0.05. the most dominant variable in this study is a variable amount of money in circulation. Based on the value of the adjusted R-square is 0872. This means that changes in the exchange rate were able to be explained by the variable interest rate bi rate, money supply and balance of payments amounted to 87.2% and the remaining 12.8% is determined by other factors.Keywords : BI Rate Interest Rate, The Amount Of Money Supply, Balance Of Payments and Exchange Rate